Implementing Scientific Approach of 2013 Curriculum at KTSP-Based School for Teaching Present Continuous Tense - Sodik, Fajar; Wijaya, M. Sayid (Universitas Islam Negeri Raden Intan Lampung, 2017)
In teaching learning process, there are a lot of students have difficulties in learning English, especially grammar. The students’ mastery in grammar at SMP Taman Siswa Teluk Betung is also still low. Therefore, the objective of the research is to know the influence of using scientific approach in curriculum 2013 towards students’ mastery in present continuous tense at the eighth grade of SMP Taman Siswa Teluk Betung in the academic year of 2015/2016. In this research, the writer used quasi experimental design by employing control group pretest-posttest design and also conducting tryout to get a good instrument. The population of this research was all students at eighth grade of SMP Taman Siswa Teluk Betung which consisted of 130 students in four classes. The writer took two classes as the sample by using cluster random sampling. In the experimental class the writer used scientific approach in curriculum 2013, whereas in the control class the writer used grammar translation method. Each class received the same pretest and posttest. There were five meetings in each class during the research, including one meeting for pretest, three meetings for treatments and one meeting for posttest. In collecting the data, the writer used test in the form of multiple choice question. The data was analyzed by using Mann-Whitney U, because the data were not in normal distribution. Based on the result of the hyphothesis test that is computated by using non-parametric statistics, Mann-Whitney U, it can be seen that the Pvalue (sig)= .000 and <α= 0.05. It means that Ha was accepted and Ho was rejected. It can be concluded that there was influence of using scientific approach in curriculum 2013 towards students’ mastery in present continuous tense at the eighth grade of SMP Taman Siswa Teluk Betung.